(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article reflects the information that the history of the development of simultaneous translation belongs not only to the recent XIX-XX centuries, but also to its distant past. Information is provided about translation and their importance in social life in the periods before and after our era.